Cardio-respiratory and haematological indices in factory workers exposed to cement dust (Nigerian Journal of Physiological Sciences, 2025)
The Nigerian cement industry, which produces 58.9 million metric tonnes annually, creates occupational health risks for workers who regularly encounter cement dust containing fine particulates with crystalline silica and heavy metals. This study aims to investigate the effect of cement dust on cardio-respiratory and haematological indices in exposed factory workers. The research design utilized a cross-sectional approach on 111 participants (60 cement factory workers (53 male, 7 female) who had at least three years of exposure and 51 control subjects (44 male, 7 female), matched by demographic characteristics and unexposed to cement dust. Pulmonary function was assessed via spirometry, cardiovascular health was evaluated using electrocardiography and measurement of blood pressure by a digital sphygmomanometer, and a haematological analysis (full blood count) was carried out using standard methods. The study data demonstrated that exposed workers experienced significant decreases in forced vital capacity (FVC), forced expiratory volume in one second (FEV1), Forced Expiratory Flow at 75% of FVC (FEF75), and peak expiratory flow, which point towards restrictive pulmonary damage. The cardiovascular evaluations revealed elevated systolic blood pressure, along with prolonged QTc intervals and reduced T-wave amplitudes. Simultaneously, the haematological assessments revealed increased red cell distribution width and changes in white blood cell counts. The results demonstrate the occupational risk factors (marked declines in lung function, disruptions in cardiac indices, and haematological abnormalities) associated with cement dust contact, highlighting the necessity for stronger industrial regulations with protective measures